2019
DOI: 10.1016/j.tins.2019.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Microbiota: Missing, or the Missing Link?

Abstract: The intrauterine environment provides a key interface between the mother and the developing fetus during pregnancy, and is a target for investigating mechanisms of fetal programming. Studies have demonstrated an association between prenatal stress and neurodevelopmental disorders. The role of the intrauterine environment in mediating this effect is still being elucidated. In this review, we discuss emerging preclinical and clinical evidence suggesting the existence of microbial communities in utero. We also ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 90 publications
0
39
0
4
Order By: Relevance
“…Furthermore, using a number of microbiological and molecular methods, researchers could not identify a microbiota in human placentas delivered at term from women who underwent caesarean delivery . Finally, recently published reviews have concluded that there is no compelling evidence to date for the existence of a universal mammalian placental or fetal microbiota …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, using a number of microbiological and molecular methods, researchers could not identify a microbiota in human placentas delivered at term from women who underwent caesarean delivery . Finally, recently published reviews have concluded that there is no compelling evidence to date for the existence of a universal mammalian placental or fetal microbiota …”
Section: Introductionmentioning
confidence: 99%
“…While there is a plethora of data demonstrating that gestational stressors affect placenta and fetal development (Brunton & Russell, 2011;Chen & Gur, 2019;Monk et al, 2012;St. Pierre et al, 2018), a stronger emphasis on identifying interventions to promote maternal/offspring protection from adverse experiences is needed (Kentner et al, 2019b;Shonkoff et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Low levels associated with decreased alveolarization and susceptibility to injury [2] amnion is now challenged by the emergence of intrauterine microbiota influencing fetal programming and development [24] and its relation to premature birth and neonatal respiratory diseases [25,26]. Premature birth causes an interruption of lung development and maturation, and at the same time exposes the neonate to profound alterations of these systems.…”
Section: Vitaminsmentioning
confidence: 99%